GLOBAL EXPERIENCE OF TAX STIMULATION OF SOFTWARE DEVELOPMENT INDUSTRY - S. Kravchuk (Вестник университета)
The article presents arguments to stimulate innovation and software development and describes main types of tax incentives for innovation activity and software development abroad. The article also draws parallels between the owners' investments and tax incentives. The types of tax incentives are examined and systematized from the point of view of their influence on the company, and recommendations on the procedure for their provision are formulated.